Small Intestinal Bacterial Overgrowth and Irritable Bowel Syndrome – An Update - Takakura, Will; Pimentel, Mark (Frontiers in Psychiatry, 2020)
Small intestinal bacterial overgrowth (SIBO) is one manifestation of gut microbiome dysbiosis and is highly prevalent in IBS (Irritable Bowel Syndrome). SIBO can be diagnosed either by a small bowel aspirate culture showing ≥103 colony-forming units (CFU) per mL of aspirate, or a positive hydrogen lactulose or glucose breath test. Numerous pathogenic organisms have been shown to be increased in subjects with SIBO and IBS, including but not limited to Enterococcus, Escherichia coli, and Klebsiella. In addition, Methanobrevibacter smithii, the causal organism in a positive methane breath test, has been linked to constipation predominant irritable bowel syndrome (IBS-C). As M. smithii is an archaeon and can overgrow in areas outside of the small intestine, it was recently proposed that the term intestinal methanogen overgrowth (IMO) is more appropriate for the overgrowth of these organisms. Due to gut microbiome dysbiosis, patients with IBS may have increased intestinal permeability, dysmotility, chronic inflammation, autoimmunity, decreased absorption of bile salts and even altered enteral and central neuronal activity. As a consequence, SIBO and IBS share a myriad of symptoms including abdominal pain, distention, diarrhea, and bloating. Furthermore, gut microbiome dysbiosis may be associated with select neuropsychological symptoms, although more research is needed to confirm this connection. This review will focus on the role of the gut microbiome and SIBO in IBS, as well as novel innovations that may help better characterize intestinal overgrowth and microbial dysbiosis.